Significance of FXa and its receptor PAR2 for the growth of colon cancer cells in vitro and in vivo - Meyer, Ulrike; Rönnpagel, Vincent; Grammbauer, Sophie; von Lucadou, Mirjam; Rauch-Kröhnert, Ursula; Schwedhelm, Edzard; Dombrowski, Frank; Ritter, Christoph; Rauch, Bernhard H. (Frontiers in Oncology, 2025)
Colon cancer is among the most common cancer types worldwide. Signaling pathways that control cell proliferation and migration play a crucial role in its progression. The G-protein-coupled protease-activated receptors (PARs) are associated mediators in this process. Both activated coagulation factors thrombin and FXa are capable of activating PARs. While thrombin, beyond its intrinsic role in hemostasis, primarily activates PAR1, FXa mediates its cellular effects independently via PAR2. Although the role of thrombin and PAR1 activation in cancer development has been established for some time, the impact of FXa-PAR2 on tumor progression represents a relatively novel area of investigation. Therefore, the current study was conducted to examine the role of FXa and PAR2 signaling in colon cancer progression using the murine colon cancer cell line MC38. Proliferation and migration assays were performed in vitro and signaling pathways analyzed by Western blot. In vivo, tumor growth and health status were investigated in WT and PAR2-KO mice. The findings demonstrate that FXa considerably augments the proliferation and migration of colon cancer (CC) cells in vitro. A molecular mechanism of action has been identified in the activation of PAR2 by FXa. The coagulation factor significantly induces MAPK- and AKT-signaling with EGFR transactivation in the murine MC38 cells utilized. Although oral treatment with a direct FXa inhibitor (Apixaban) at a dosage of up to 50 mg/kg did not significantly affect tumor growth in vivo, PAR2 deficiency resulted in significantly reduced tumor growth and enhanced health condition status, indicating a key role of PAR2 in the progression of colon cancer.